Trends in hours and economic growth - L. Rachel Ngai; Christopher A. Pissarides (Institute for the Study of Labor (IZA), 2007)
We study long-run trends in market hours of work and employment shifts across economic sectors driven by uneven TFP growth in market and home production. We focus on the substitutions between market and home production and on the structural transformation between agriculture, manufacturing and services. The model can rationalize the observed falling or U-shaped pattern for aggregate hours, the complete marketization of agriculture and manufacturing, and the shift from agriculture to services without violating balanced aggregate growth. We find support for the model's predictions in long-run US data.
urn:nbn:de:101:1-2008042900
Keywords: 330; Arbeitszeit; Produktivität; Strukturwandel; Haushaltsproduktion; Freizeit; Wirtschaftswachstum; Wachstumstheorie; USA; Industriestaaten